2016
DOI: 10.1002/anie.201605924
|View full text |Cite
|
Sign up to set email alerts
|

Highly Conformal Deposition of an Ultrathin FeOOH Layer on a Hematite Nanostructure for Efficient Solar Water Splitting

Abstract: An ultrathin (ca. 2 nm) amorphous FeOOH overlayer was deposited conformally on a hematite nanostructure by a simple solution-based precipitation method, to generate an oxygen evolution cocatalyst for efficient solar water splitting. This uniform and highly conformal coating of the ultrathin metal oxyhydroxide is rare and is distinguished from the layers prepared by other conventional methods. With the FeOOH overlayer as the cocatalyst, the water oxidation photocurrent of hematite increased by a factor of appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
186
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 223 publications
(193 citation statements)
references
References 38 publications
7
186
0
Order By: Relevance
“…Similarly, photoelectrodeposited Co-Pi caused 170 mV improvement 29 whereas FeOOH cocatalyst shied the onset potential by 120 mV. 30 It is also reported that photo or electrochemical deposition of Nioxides or Co-oxides on hematite could lower the required bias voltage by 100-300 mV. (Fig.…”
Section: Effect Of Ir-pi Deposition On Pec Activitymentioning
confidence: 86%
“…Similarly, photoelectrodeposited Co-Pi caused 170 mV improvement 29 whereas FeOOH cocatalyst shied the onset potential by 120 mV. 30 It is also reported that photo or electrochemical deposition of Nioxides or Co-oxides on hematite could lower the required bias voltage by 100-300 mV. (Fig.…”
Section: Effect Of Ir-pi Deposition On Pec Activitymentioning
confidence: 86%
“…[33,73,101,[171][172][173][174][175][176] It has potential advantages such as feasible synthesis, well stability, and resource abundancy. [33,73,101,[171][172][173][174][175][176] It has potential advantages such as feasible synthesis, well stability, and resource abundancy.…”
Section: Iron-based Oxyhydroxidementioning
confidence: 99%
“…[18,19] Therefore, designing composited photoanodes with proper band-gap energy structure is considered to be a promising route to overcome these limitations induced poor PEC performance. [8,32,33] Recently, the outstanding OER performance Water Splitting Particularly, benefiting from the outstanding visiblelight response performance and carrier mobility within silicon, it has long been regarded as the most suitable material to build the solar energy conversion device.…”
mentioning
confidence: 99%
“…[26] As the conduction band (CB) of silicon is more negative than most of the common MO semiconductors (e.g., TiO 2 , [27,28] WO 3 ), [29] silicon can bring better electron reduction kinetics on the counter electrode. [8,32,33] Recently, the outstanding OER performance Water Splitting [23,31] In this regard, constructing MO/Si heterostructured photoanode is proposed to overcome the potential shortcomings of both MO and silicon simultaneously.…”
mentioning
confidence: 99%
See 1 more Smart Citation